Tying Up the Loose Ends: The Determinants of Active Labour Market Policy in the Western Countries 1985-2013 - Ari-Matti Näätänen (The Canadian Center of Science and Education (CCSE), 2022)
Knowledge on the determinants of Active Labour Market Policy (ALMP) spending accumulated during the 2000s. Despite these advances, the current research lacks a systematic approach to the relevant determinants. This article fills the research gaps by analysing simultaneously the 14 most frequently used determinants for the first time. In addition to these variables, this study introduces a new factor, namely the impact of economic crises. Through the analysis of the longest data period yet investigated of 20 Western countries and a comparison of methodological alternatives, this study both challenges and reinforces previous findings, as well as produces new ones. For example, it is the first investigation to reveal the positive effect of government indebtedness and economic crises on ALMP expenditure. However, the rivalry between the “usual suspects” continues, as the negative effects of budget deficits, foreign trade, and population ageing, and the positive effects of trade union density and GDP growth, were rediscovered in this analysis.